2021
DOI: 10.1002/jhet.4243
|View full text |Cite
|
Sign up to set email alerts
|

Conformational analysis of 2,5‐diaryl‐4‐methyl‐2,4‐dihydro‐3H‐1,2,4‐triazol‐3‐ones: Multinuclear NMR and DFT calculations

Abstract: Conformational exploration of five 2,5‐diaryl‐4‐methyl‐2,4‐dihydro‐3H‐1,2,4‐triazol‐3‐ones has been carried out based on a combination of their NMR chemical shifts determined in CDCl3 and the scrutiny of their computed relative energies and absolute shieldings calculated at the DFT/GIAO/B3LYP/6–311++G(d,p) level. The very flat potential energy curves corresponding to the three relevant single bond rotations were explored by calculating the energy of the rotational barriers and comparing the experimental chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…68 As revealed by Gerothanassis, 69 revision of structure of geometric isomers of conjugated linolenic acids, hexadecatrienyl pheromones, and model triene-containing compounds was achieved as a result of close symbiosis between experimental and theoretical NMR approaches. Claramunt et al 70 reported on multinuclear NMR and DFT calculations supporting the conformational analysis of 2,5-diaryl-4-methyl-2,4-dihydro-3H-1,2,4-triazol-3-ones. The loliolide molecule and its isomers were studied theoretically and their nuclear shieldings were predicted.…”
Section: Dft Studies Of Nuclear Shieldingmentioning
confidence: 89%
“…68 As revealed by Gerothanassis, 69 revision of structure of geometric isomers of conjugated linolenic acids, hexadecatrienyl pheromones, and model triene-containing compounds was achieved as a result of close symbiosis between experimental and theoretical NMR approaches. Claramunt et al 70 reported on multinuclear NMR and DFT calculations supporting the conformational analysis of 2,5-diaryl-4-methyl-2,4-dihydro-3H-1,2,4-triazol-3-ones. The loliolide molecule and its isomers were studied theoretically and their nuclear shieldings were predicted.…”
Section: Dft Studies Of Nuclear Shieldingmentioning
confidence: 89%
“…The absolute chemical shieldings have been calculated for the gas phase, while the chemical shifts correspond to values determined in the solution. The chemical shifts taking into account solvent effects were not calculated because if the absolute chemical shieldings were calculated with a general solvent model like the polarizable continuum model (PCM, THF, MeOH, and H 2 O) 18 the results do not improve and in most cases get worse 19 …”
Section: Methodsmentioning
confidence: 99%